Features of cross-cultural approach in the process of teaching foreign languages (Pedagogy of Higher and Secondary Education, 2011)
The article defines the essence of the notions “approach”, “culture”, crosscuitural “approach”, reveals the main peculiarities of the crosscuitural approach and its role in foreign language teaching.
Keywords: approach; culture; crossculture; multiculturalism; crosscultural approach